Municipal sustainable development and bank financing:: analysis of the Green Municipalities Program in Pará - Vale, Vanessa Paiva Costa; Vinagre, Marco Valério de Albuquerque; Lobo, Marco Aurélio Arbage; Bello, Leonardo Augusto Lobato; Lima, Alberto Carlos de Melo (Sustainability in Debate, 2018)
The concern over sustainable development in the world and in Brazil has made possible the creation of The Green Municipality Program in the State of Pará. The program combats deforestation in the state and encourages environmental resource management. The objective of this study is to analyze the level of sustainability of the green municipalities of Pará in relation to bank financing to promote sustainable development. The study was conducted applying the Pearson Correlation after creating sustainable development indexes for 13 municipalities that received bank financing in 2010. The results obtained demonstrated indexes between 0.3773, considered as a level of alert, and 0.5310, as an acceptable level. The results show a weak correlation of higher level of municipal sustainability with the access to bank financing for this purpose. The study points to the need for banks to revise their current guidelines for financing municipal sustainable development to promote economic, social, cultural, and environmental development.